Discernment and biblical spirituality - An application discernment in the milieu and wake of Nehemiah 8 - Lombaard, Christo 1966- (2015)
In this contribution, as the culmination of a research project on discernment, theologically considered, the conceptual and methodological insights gained in the preceding publications are here brought to bear on a biblical text as a means of applying these insights exegetically. This application however does not occur in an exegetical research vacuum: key moments in Hebrew Bible research history are therefore taken into brief review and placed within the light of the most recent insights on the sociological scenario within post-exilic Israel. Within this ancient context, the different modes of divine communication, namely mediated through Scriptures or experienced through direct revelation, was at times a point of intense contestation, as it is in the modern world. This prophetic-Mosaic dispute forms the theological background to Nehemiah 8, as a textual attempt in post-exilic Israel to find a median position between these two contested forms of discerning in the most valid way the divine will.
Keywords: Biblical Spirituality; Charismatic revelation; Discernment; Divine communication; Inner-biblical contestation; Nehemiah 8; Orthodoxy; Torah versus prophecy